2019
DOI: 10.1038/s41598-019-39298-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key lncRNAs contributing to diabetic nephropathy by gene co-expression network analysis

Abstract: LncRNA is reported to have important role in diabetic nephropathy (DN). Here, we aim to identify key lncRNAs of DN using bioinformatics and systems biological methods. Method: Five microarray data sets from Gene Expression Omnibus (GEO) database were included. Probe sets were re-annotated. In the training set, differential expressed genes (DEGs) were identified. Weighted gene co-expression network analysis (WGCNA) was constructed to screen diabetic-related hub genes and reveal their potential biological functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…11,16 One such lncRNA, lnc-ISG20 was documented to exhibit up-regulated expression levels in the glomerular of DN patients, while miR-486-5p was correlated with blood glucose or albuminuria, all of which enable non-coding RNAs to serve as promising biomarkers for DN or renal fibrosis. 7,24 However, the underlying mechanisms of lnc-ISG20 and miR-486-5p in regard to DN remain to be uncovered. In view of this, the current study performed a series of experiments, and our findings demonstrated that lnc-ISG20 was highly expressed in DN patients, and exhibited a close relationship with renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…11,16 One such lncRNA, lnc-ISG20 was documented to exhibit up-regulated expression levels in the glomerular of DN patients, while miR-486-5p was correlated with blood glucose or albuminuria, all of which enable non-coding RNAs to serve as promising biomarkers for DN or renal fibrosis. 7,24 However, the underlying mechanisms of lnc-ISG20 and miR-486-5p in regard to DN remain to be uncovered. In view of this, the current study performed a series of experiments, and our findings demonstrated that lnc-ISG20 was highly expressed in DN patients, and exhibited a close relationship with renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…As to DN, lncRNA ZEB1-AS1 has been shown to enhance the expression of ZEB1 by promoting H3K4me3 histone modification on its promoter during high glucose treatment with increased ZEB1 exerting an anti-fibrotic role [42]. Importantly, since all of these data were primarily obtained in mouse models, a number of expression screens in DN have been able to show evolutionary conservation of lncRNA modulation in human datasets [43,44,45] indicating the future potential of data obtained in mouse models for the patient setting.…”
Section: Lncrnas In Glomerular Diseasementioning
confidence: 99%
“…Its pathological features include degeneration of articular cartilage, synovial inflammatory infiltration and secondary osteophyte formation. Patients with this disease are often accompanied by chronic pain, poor flexion and extension of knee joints, and the late course of the disease can also incur limited range of movement or even disability [3,4]. Currently, the majority of KOA patients are the middle-aged and the elder people.…”
Section: Introductionmentioning
confidence: 99%